2012
DOI: 10.4314/ijbcs.v6i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical monitoring of methyl parathion degradation based on carbon fiber microelectrodes (CFME)

Abstract: The electrochemical degradation of methyl parathion (MP) has been investigated by using carbon fiber microelectrodes (CFME) as working electrode and acetate buffer pH 5.2 as supporting electrolyte. pnitrophenol (PNP) and p-aminophenol (PAP) recognized as by-products of MP degradation process have been detected and identified in real time using square wave voltammetry. This study shows for the first time that CFME could be used to follow MP degradation in real time and to identify its stables metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…Par ailleurs, il est bien connu dans la littérature que l'électrochimie est une technique utilisée pour l'analyse de composés électro-actifs dans diverses matrices (Tapsoba et al, 2009;Ouedraogo et al, 2013), parfois couplée à la chromatographie liquide comme détecteur (Wu et al, 2007;Novaka et al, 2008;Zielińska et al, 2008;Konieczy-Ski 2015). En effet, Tapsoba et al (2012aTapsoba et al ( , 2012b dans leurs travaux, ont exploité l'électrochimie pour analyser les résidus de pesticides organophosphorés dans les eaux et les sols. Bako et al (2017) quant à eux, ont utilisé les microélectrodes à fibre de carbone modifiées par un polymère de phtalocyanine de nickel tétrasulfonée pour analyser le 3-méthyl-4nitrophénol, métabolite du fénitrothion dans les eaux en suivant l'oxydation du groupement hydroxyle.…”
Section: Introductionunclassified
“…Par ailleurs, il est bien connu dans la littérature que l'électrochimie est une technique utilisée pour l'analyse de composés électro-actifs dans diverses matrices (Tapsoba et al, 2009;Ouedraogo et al, 2013), parfois couplée à la chromatographie liquide comme détecteur (Wu et al, 2007;Novaka et al, 2008;Zielińska et al, 2008;Konieczy-Ski 2015). En effet, Tapsoba et al (2012aTapsoba et al ( , 2012b dans leurs travaux, ont exploité l'électrochimie pour analyser les résidus de pesticides organophosphorés dans les eaux et les sols. Bako et al (2017) quant à eux, ont utilisé les microélectrodes à fibre de carbone modifiées par un polymère de phtalocyanine de nickel tétrasulfonée pour analyser le 3-méthyl-4nitrophénol, métabolite du fénitrothion dans les eaux en suivant l'oxydation du groupement hydroxyle.…”
Section: Introductionunclassified
“…Simple and advantageous alternatives are electrochemical techniques due to their low cost, high sensitivity and specificity and they do provide fast and reliable analysis [2] [3] [4] [8] [9]. Several studies reported that organophosphate compounds can be detected electrochemically using CFME [5] [10] [11] and CFME modified by use of polymers, enzymes and mercury to improve their sensitivity and selectivity [6] [7] [12] [13]. In previous work, we report the use of CFME modified by nickel tetrasulfonated phthalocyanine polymer (p-NiTSPc) film for methylparathion and its metabolite p-nitrophenol in water [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fenitrothion, an organophosphate insecticide is widely used in cotton cultivation in the north of Burkina Faso in the fight against locust attack. It is well-known that it possesses some toxicity because it acts as acetylcholinesterase inhibitors and its residues and metabolites are present in food chain and environment [2] [3] [4] [5]. Thus, to limit the impact of pesticides on the environment and human health, analytical techniques have been developed to detect their presence and quantify pesticide residues in waters, soils, foods.…”
Section: Introductionmentioning
confidence: 99%